THE INFLUENCE OF CONSUMER ETHNOCENTRISM AND PERCEIVED QUALITY: A STUDY ON THE PURCHASE DECISION OF LOCAL COSMETIC MAKE OVER - Viola De Yusa (International Journal of Economics, Business, and Entrepreneurship, 2021)
Competitiveness in the global cosmetics sector is rising fast in Indonesia, as evidenced by an increase in the degree of competition among cosmetic enterprises. Indonesians have long believed that imported goods are superior than locally produced goods. Make Over is a local Indonesian cosmetics brand. The purpose of this study is to examine the impact of customer ethnicity and perceived quality on the purchase of Make Over cosmetic items. This form of study employs quantitative methods. In this study, 170 respondents from Lampung who used Make Over cosmetics were utilized as examples. This study's population consists of Make Over cosmetic product users. Purposive sampling is used in this study. Partial Least Squares SEM was used to analyze the data. The findings of the study show that customer ethnocentrism and perceived quality have an impact on the purchase decisions of Make Over cosmetic goods in Lampung. The stronger the customer's ethnocentrism, the more likely the consumer would choose to use local cosmetics created in the nation, such as Make Over, rather than buying foreign-made or imported cosmetics. The better the perceived quality of a thing, the more likely it will be purchased. The stronger the customer's ethnocentrism, the more likely the consumer would choose to use local cosmetics created in the nation, such as Make Over, rather than buying foreign-made or imported cosmetics. The better the perceived quality of a thing, the more likely it will be purchased. The more the customer's ethnocentrism, the more likely the consumer would choose to utilize local cosmetics created in the nation, such as Make Over, rather than purchasing cosmetic items made elsewhere or imported cosmetics. The better the perceived quality of the product, the more probable it is that the product will be purchased.